Photoluminescence Sensing of Chloride Ions in Sea Sand Using Alcohol-Dispersed CsPbBr3@SiO2 Perovskite Nanocrystal Composites - Henggan Li; Feiming Li; Yipeng Huang; Linchun Zhang; Min Ye; Jingwen Jin; Xi Chen (Chemosensors, 2022)
In this study, CsPbBr3@SiO2 perovskite nanocrystal composites (CsPbBr3@SiO2 PNCCs) were synthesized by a benzyl bromide nucleophilic substitution strategy. Homogeneous halide exchange between CsPbBr3@SiO2 PNCCs and Cl− solution (aqueous phase) was applied to the determination of Cl− in sea sand samples. Fast halide exchange with Cl− in the aqueous phase without any magnetic stirring or pH regulation resulted in the blue shift of the photoluminescence (PL) wavelength and vivid PL color changes from green to blue. The results show that the PL sensing of Cl− in aqueous samples could be implemented by using the halide exchange of CsPbBr3@SiO2 PNCCs. A linear relationship between the PL wavelength shift and the Cl− concentration in the range of 0 to 3.0% was found, which was applied to the determination of Cl− concentration in sea sand samples. This method greatly simplifies the detection process and provides a new idea for further broadening PL sensing using the CsPbBr3 PNC halide.